EFFICACY OF MICRO-NEEDLING ON POST ACNE SCARS - Khalid, Farrukh Aslam; Ahmad, Sania; Mehrose, Muhammad Younas; Saleem, Muhammd; Yousaf, Muhammad Amin; Mujahid, Abdul Malik; Rehman, Saif ur; Tarar, Moazzam Nazeer (Journal of Ayub Medical College Abbottabad, 2019)
Background: Acne effects 80-90% of teenage population all around the world. Resulting scars can lead to facial disfigurement and psychological issues in affected population. To counter this problem many treatment options have been tried including resurfacing lasers, dermabrasion, peeling, fillers, platelet rich plasma therapy etc. All have shown variable results. Among these modalities, micro needling is showing promising results in treatment of acne scars due to collagen induction. This study was conducted to assess efficacy and safety of micro-needling on acne scars. Methods: In this cross-sectional study a total of 50 patients (female 35, male 15) underwent treatment for post acne scarring, 4 sessions of micro-needling were done under local anaesthesia 3 weeks apart over the span of 2 months. Initial and follow up qualitative assessment was done. Photographs were taken of each patient on their subsequent visit, they were analysed and compared for final results. Grading was done by using Goodman Baron scale. Results: 70% (35) were females and 30% (15) were males with mean age of 27.31±4.41 ranging from 19-35 years. After the treatment of scars, 73% (08) of Grade 4 scars have showed improvement by 2 grades, remaining 27% (03) showed improvement to Grade 3. In 20 patients with Grade 3 scars, 30% (06) showed improvement by 1 grade. Remaining 70% (14) improved by 2 grades. All patients with Grade 2 scar downgraded to grade 1 after treatment. Chi-square test was used to assess pre-treatment and post treatment grading improvement among subjects and was statistically significant. (X2=30.010 p=000). Conclusion: Micro needling is an effective tool for aesthetic improvement of post acne scarring. Keywords: Acne; Acne scarring; Micro-needling Acne; Acne scarring; Micro-needling